The Influence of Self-Efficacy, Growth Mindset, and Adaptability on the Human Capital of MSME Entrepreneurs in Makassar City, with Digital Literacy as a Moderating Variable - Firman Karim; Akhmad; Andi Rustam (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study examines the effects of self-efficacy, growth mindset, and adaptability on human capital, with digital literacy serving as a moderating variable among Micro and Small Enterprises (MSEs) in Makassar City, Indonesia. A quantitative explanatory research design was employed. Data were collected through structured questionnaires administered to 200 MSE owners selected using purposive sampling. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The findings reveal that self-efficacy, growth mindset, and adaptability have positive and significant effects on human capital. Furthermore, digital literacy significantly strengthens the relationships between self-efficacy and human capital, as well as between adaptability and human capital. However, digital literacy does not moderate the relationship between growth mindset and human capital. The structural model demonstrates strong explanatory power, with an R² value of 0.881, indicating that the proposed model explains 88.1% of the variance in human capital. These findings highlight that strengthening human capital in MSEs requires not only psychological and adaptive capabilities but also digital competencies to enhance business competitiveness in the digital transformation era. The study offers practical implications for policymakers and business development institutions in designing integrated human capital development and digital literacy programs for MSEs.